DEVELOPMENT OF SILK FIBROIN SCAFFOLD FOR CARTILAGE TISSUE ENGINEERING APPLICATION - Ari Wibowo, Untung
Porous scaffold is required in cartilage tissue engineering to fulfill the shortage of current gold standard of cartilage deficiency treatment. Silk fibroin has great potential to be used as scaffold materials since known by its high strength, biocompatibility, and biodegradability. The silk fibroin porous scaffold has been widely studied. However, they were processed using traditional LiBr of CaCl2/H2O/Et-OH which wasting 5-8 days. Previous study showed the porous scaffold has been developed using faster direct dissolution using formic acid-CaCl2 and salt leaching. However, the pores were very small (~5 µm) and less interconnected. In this study, larger salt size158-503 µm, silk concentration of 2-12 w/v%, and higher salt to silk ratio 5:1 (g/ml) will be used for improving the pore morphology. Evaluation on the pore formation was examined using the Scanning Electron Microscopy (SEM. Characterization on the scaffold were undertaken using Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), and Thermo-Gravimetric Analysis (TGA). The hydrophilicity properties were measured using static contact angle on the film, and using the measurement of water uptake and infiltration on the porous scaffold. The degradation of the scaffolds was evaluated in several enzymes including ?-chymotrypsin, Collagenase IA, and Protease XIV. Evaluation of the scaffold’s biocompatibilities were assessed by means of the observation on the Adipose-derived Stem Cell (AdSCs) attachment and proliferation. Porous silk fibroin scaffolds fabricated using salt leaching and direct dissolution methods have been successfully conducted with the minimum silk fibroin concentration 6 w/v%. The resulted scaffolds have highly interconnected and open pore morphology with the pore size of 160-536 µm, which suitable for cartilage tissue engineering. FT-IR, XRD, DSC, and TGA characterization revealed the scaffold’s intrinsic secondary structure compared to the fiber. The silk film exhibited hydrophilic water contact angle of 49-58° and the scaffold showed high water uptakes of 81-96% due to the highly interconnected pore. The scaffolds were degraded aggressively in Protease XIV with 56% mass loss followed by ?-Chymotrypsin and Collagenase IA at about 19% and 12% mass loss, respectively. AdSCs cells showed strong attachment and good proliferation on the resulted scaffold which indicated good biocompatible behavior. The highest AdSCs proliferation were revealed on the scaffold with silk concentration of 12 w/v% and pore size of 500 µm. The suitable pore morphology, high water-infiltration ability and biocompatibility of the scaffolds indicating its potential for used in cartilage tissue engineering.